Dielectric and piezoelectric properties of BiFeO3 from molecular dynamics simulations. (September 2015) - Graf, M.; Sepliarsky, M.; Machado, R.; Stachiotti, M.G.
Abstract: A first-principles based atomistic scheme is used to investigate the dielectric and piezoelectric properties of BiFeO3 . The atomistic model fitted from first-principles calculations reproduces very well the structural and polar properties of the material at finite temperature, predicting a direct transition from a low-temperature R3c ferroelectric phase to a Pbnm orthorhombic phase in agreement with experiments. We use this theoretical approach to calculate intrinsic single crystal properties, which are difficult to obtain from experiments due to decomposition and leakage problems. The whole set of dielectric and piezoelectric coefficients for BiFeO3 is computed as a function of temperature, together with the orientation dependence of the longitudinal coefficient d 33 ⁎ . Highlights: An atomistic model for BiFeO3 is used to calculate single crystal properties. Dielectric and piezoelectric coefficients are computed at finite temperature. The orientation dependence of the longitudinal coefficient d 33 ⁎ is calculated.